Partial replacement of EPR by GTR in highly flowable PP/EPR blends: Effects on morphology and mechanical properties - Lima, Paulo Silva
This research analyzes the effect of ground tire rubber (GTR) and a novel metallocene-based ethylene-propylene copolymer (EPR), with high propylene content, on the morphology and mechanical behavior of ternary polymer blends based on a highly flowable polypropylene homopolymer (PP). The PP/EPR blends morphology, with very small domains of EPR dispersed in the PP matrix, indicates a good compatibility among these materials, which leads to a significant improvement on elongation at break and impact strength. The incorporation of EPR on the rubber phase of thermoplastic elastomeric blends (TPE) based on GTR and PP (TPEGTR) has a positive effect on their mechanical performance, attributed to the toughness enhancement of the PP matrix and to the establishment of shell-core morphology between the rubber phases. The mechanical properties of the ternary blends reveal that TPEGTR blends allow the upcycling of this GTR material by injection molding technologies. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42011.